Wykonaj mnożenie:
a) 2(a+b)
b)-3(x+y)
c)-5(min)
d)-6(-c-d)
e)1/2(4x-2)
f)-2/3(6a-12b)
g)(c-2d)*(-0,5)

Usuń nawiasy i wykonaj redukcją wyrazów podobnych:
a)3x-4(y-3x)
b)8(-12x+y)+12x
c)3(a-3b)-4(2b-4x)
d)-5(4a-3b)-4(5a-5b)
e)-3x(2x-3y)+2x(-3x-5y-1)
f)-2x(x-5y-3)+3x(x+5y+2)

2

Odpowiedzi

2010-03-07T11:31:57+01:00
Wykonaj mnożenie:
a) 2(a+b)=2a+2b
b)-3(x+y)=-3x-3y
c)-5(min)=-5min
d)-6(-c-d)=6c+6d
e)1/2(4x-2)=2x-1
f)-2/3(6a-12b)=-4a+8b
g)(c-2d)*(-0,5)=-0,5c-1d

Usuń nawiasy i wykonaj redukcją wyrazów podobnych:
a)3x-4(y-3x)=3x-4y+12x=-4y+15x
b)8(-12x+y)+12x=-96x+8y+12x=-84x+8y
c)3(a-3b)-4(2b-4x)=3a-9b-8b+16x=3a-17b+16x
d)-5(4a-3b)-4(5a-5b)=-20a+15b-20a+10b=-40a+25b
e)-3x(2x-3y)+2x(-3x-5y-1)=-6x^2+9xy-6x^2-10xy-2x=-12x^2-xy-2x
f)-2x(x-5y-3)+3x(x+5y+2)=-4x^2+10xy+6x+3x^2+10xy+6x=-x^2+20xy+12x
23 3 23
2010-03-07T11:51:54+01:00
1. a)2(a+b)=2*a+2*b=2a+2b
b)-3(x+y)=(-3)*x+(-3)*y=-3x-3y
c)-5(min)=-5m-5i-5n
d)-6(-c-d)=6c+6d
e)1/2(4x-2)= 2x-1
f)-2/3(6a-12b)=-2a+4b
g)(c-2d)*(-0,5)=-0,5c+1d
2.a)3x-4(y-3x)=3x-4y+12x=15x-4y
b)8(-12x+y)+12x=-96x+8y+12x=-84x+8y
c)3(a-3b)-4(2b-4x)=3a-9b-8b+16x=3a-17b+16x
d)-5(4a-3b)-4(5a-5b)=-20a+15b-20a+20b=-40a+35b
e)-3x(2x-3y)+2x(-3x-5y-1)=-6x(kwadrat)+9xy-6x(kwadrat)-10xy-2x=-12x(kwadrat)-xy-2x
f)-2x(x-5y-3)+3x(x+5y+2)=-2x(kwadrat)+10xy+6x+3x(kwadrat)+15xy+6x=-x(kwadrat)+25xy+12x



19 4 19